Analysis of Water Quality in Carp (Cyprinus carpio L.) Nursery Ponds - Deo Sandika; Dewa Gede Semara Edi; I Made Kawan (Gema Agro, 2024)
This research is a case study which aims to determine the condition of water quality in seeding ponds for Carp Fish (Cyprinus carpio L.). This research was conducted 21 days in June 2023 at the UPTD. Produksi Perikanan Budidaya Provinsi Bali. This research design is divided into 4 stages, start with preparation, implementation, data analysis and conclusions. Water quality observations include several physical, chemical and biological parameters. The variables observed were temperature, brightness, pH, ammonia and plankton abundance. The aim of this research is to determine the condition of water quality at the research location, determine daily water quality fluctuations and also determine the relationship between water quality variables. Based on the results of observations, it is known that the average temperature value reached 27.7Â°C, the average brightness was 36.7 cm, the average pH was 7.2, the average ammonia was 0.15 and the average abundance plankton reached 1,119 cells/L. It is known that there are quite significant fluctuations in water quality variables both on a daily basis and during the research period, and it is also known that there